Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Cardiac Organoids Uncover an Association of CHD7 Deficiency with Congenital Heart Disease - Siyu Sun; Zhiyu Feng; Weilan Na; Yuan Gao; Shaojie Min; Quannan Zhuang; Siyi Lin; Quming Zhao; Xianghui Huang; Hongmei Song; Wei Sheng; Guoying Huang (Phenomics, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

A field UAV system (FUAS) with dual spectrometers for BRDF measurement - Xiuqing Hu; Xingwei He; Yuechao Sheng; Na Xu; Lin Chen; Wenjie Hu; Bingcheng Tao; Lu Zhang; Ling Wang; Yuqing He; Zhongqiu Sun (International Journal of Remote Sensing, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Mito-Apocynin Protects Against Kainic Acid-Induced Excitotoxicity by Ameliorating Mitochondrial Impairment - Miaomiao Lin; Huanchen Wu; Xiaorui Wan; Na Liu; Yiyue Jiang; Yichao Sheng; Jing Wang; Haidong Xu; Jie Xue; Zhenghong Qin; Yan Wang (Molecular Neurobiology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

MST1R Gene Variants Predispose Individuals to Tetralogy of Fallot - Zhiyu Feng; Xianghui Huang; Yuan Gao; Han Gao; Weilan Na; Chaozhong Tan; Shaojie Min; Yuquan Lu; Quannan Zhuang; Siyi Lin; Xiaojing Ma; Weicheng Chen; et al. (Phenomics, 2024)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart malformation. While a few susceptibility genes for TOF have been identified, research on the genetic basis of TOF is limited. The Macrophage stimulating 1 receptor ( MST1R ) gene encodes the macrophage-stimulating protein receptor with tyrosine phosphatase activity that is involved in immune defense. In this study, we performed whole-exome sequencing (WES) on 10 TOF families and 50 sporadic TOF patients and identified a recessive homozygous missense mutation in MST1R , c.T2009G: p.V670G, in two offspring with TOF in a single family. Targeted sequencing of the MST1R gene showed enrichment for rare variants in 417 TOF patients compared with East Asians in Genome Aggregation Database Version 2 (gnomADv2_EAS). MST1R -deficient human induced pluripotent stem cells (hiPSCs) maintained normal pluripotency but differentiated into non-functional cardiomyocytes (CMs). Taken together, our findings indicate that MST1R may play a critical role in cardiac differentiation and genetic variations in MST1R may be associated with the pathogenesis of TOF.

Influence of arbuscular mycorrhizal fungi on root foraging and competitive ability depends on soil phosphorus distribution: evidence from two pairs of invasive and native plants - Na-Na Yao; Ao Liu; Xiao-Jing Wang; Hao-Hui Deng; Sheng-Qi Fan; Hai-Jie Zhang; Hui-Xuan Liao; Shao-Lin Peng; Bao-Ming Chen (Applied Soil Ecology, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Machine learning-based mRNA signature in early acute myocardial infarction patients: the perspective toward immunological, predictive, and personalized - Hai-Hua Pan; Na Yuan; Ling-Yan He; Jia-Lin Sheng; Hui-Lin Hu; Chang-Lin Zhai (Functional & Integrative Genomics, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

bHLH genes polymorphisms and their association with growth traits in the Pacific oyster Crassostrea gigas - Na Chen; Li Li; Chenghua Li; Zhihua Lin; Jie Meng; Sheng Liu; Kai Song; Yongbo Bao (Journal of Oceanology and Limnology, 2020)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Biodegradation of malachite green by Pseudomonas sp. strain DY1 under aerobic condition: characteristics, degradation products, enzyme analysis and phytotoxicity - Lin-Na Du; Sheng Wang; Gang Li; Bing Wang; Xiao-Ming Jia; Yu-Hua Zhao; Yun-Long Chen (Ecotoxicology, 2011)

Artificial Gynogenesis and Sex Determination in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Yong-Sheng Tian; Jing-Feng Yang; Chang-Wei Shao; Xiang-Shan Ji; Jie-Ming Zhai; Xiao-Lin Liao; Zhi-Meng Zhuang; Peng-Zhi Su; Jian-Yong Xu; Zhen-Xia Sha; Peng-Fei Wu; et al. (Marine Biotechnology, 2009)

Stereoselective glucuronidation of carvedilol by Chinese liver microsomes - Lin-ya You; Chun-na Yu; Sheng-gu Xie; Shu-qing Chen; Su Zeng (Journal of Zhejiang University-SCIENCE B, 2007)

Transgenic resistance to Cymbidium mosaic virus in Dendrobium expressing the viral capsid protein gene - Chen Chang; Ying-Chun Chen; Yau-Heiu Hsu; Jian-Tai Wu; Chung-Chi Hu; Wei-Chin Chang; Na-Sheng Lin (Transgenic Research, 2005)

Heterotrimeric G-protein and signal transduction in the nematode-trapping fungus Arthrobotrys dactyloides - Tsung-Hsien Chen; Chan-San Hsu; Pui-Jen Tsai; Yi-Feng Ho; Na-Sheng Lin (Planta, 2001)

A Defective RNA Associated with Bamboo Mosaic Virus and the Possible Common Mechanisms for RNA Recombination in Potexviruses - Ting-Yu Yeh; Biing-Yuan Lin; Ya-Chun Chang; Yau-Heiu Hsu; Na-Sheng Lin (Virus Genes, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)